Akibat Hukum Perjanjian Jual Beli Online terhadap Kerusakan Barang dalam Perspektif Prinsip Strict Liability - Elko Mamesah; Muhammad Hero Soepeno; Presly Prayogo; Royke Yesdaven Jeremia Kaligis; Mario Gerson Mangowal (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Online buying and selling transactions have become a dominant practice in economic activities, yet they raise legal issues when consumers receive damaged goods. This study analyzes the legal consequences of online sale and purchase agreements for damaged goods from the perspective of the strict liability principle. The research employs normative legal research using statutory and conceptual approaches. The findings show that damage to goods gives rise to the seller’s liability as an inherent business risk without requiring proof of fault. The application of strict liability provides more effective consumer protection and enhances legal certainty in resolving online transaction disputes.